Alternative Solutions to Optimalisation of the Gassing-up Operation After Tanks Inerting Using Pressure Swing Adsorption (PSA) and Membrane Techniques - Wieczorek, A. (Scientific Journal of Gdynia Maritime University, 2018)
The article constitutes the introduction to finding a solution to a problem concerning carrying gassing-up operation in a more efficient way in terms of loosing ethylene cargo. To begin with, the impact of nitrogen presence on ethylene cascade cycle’s technical work and cooling capacity has been described. Further, the results of investigation into methods of nitrogen removing from cargo tanks after gassing-up have been presented. Possibility of pressure swing adsorption (PSA) and membrane techniques use has been analyzed with reference to ethylene carriers.